SISTEM PENGELOLAAN SAMPAH KOTA DI KABUPATEN BEKASI – JAWA BARAT - Setiyono, Setiyono (Jurnal Teknologi Lingkungan, 2001)
Recently, problems of municipal solid waste have appeared in the indonesianmetropolitan city, such as Jakarta and Surabaya. The bad of solid wastemanagement system in those city has affected the environmental quality especially in the final disposal site. The district of Bekasi, the one of big cities in Indonesia, has the same system of solid waste management with other cities in collecting, transporting and discarding of the wastes. To avoid arising the final disposal problems, Bekasi district government has improved the municipal solid waste management by upgrading of the open dumping system’s Burangkeng final disposal site into sanitary landfill system.